Resident Accuracy of Musculoskeletal Palpation With Ultrasound Verification. (27th December 2017) - Mehta, Priyesh; Rand, Ethan B.; Visco, Christopher J.; Wyss, James
Abstract : Objectives: The purpose of this observational study was to determine the accuracy of musculoskeletal palpation of the medial joint line of the knee, medial patellar tendon, and posterior tibialis tendon verified by ultrasound imaging among physical medicine and rehabilitation residents. Methods: Eighteen physical medicine and rehabilitation resident physicians at a single specialized institution were asked to identify the medial joint line of the knee, medial patellar tendon, and posterior tibialis tendon on 2 separate standardized patient models during a single data collection. They were asked to place a paper clip flat on the surface of the skin parallel to the specified anatomic structure. A high‐frequency linear array transducer was used to identify whether the paper clip was correctly placed over the structures and to measure the distance from the intended structure. Results: The accuracy rates for palpation of the medial joint line, medial patellar tendon, and posterior tibialis tendon in both models were 14%, 36%, and 28%, respectively, for all levels of residents. Accuracy rates for all of the structures by level of education were 19%, 29%, and 31% for postgraduate years 2, 3, and 4. Median confidence scores were 3.75, 3.5, and 2 for the medial joint line, medial patellar tendon, and posterior tibialis tendon. Conclusions: This study highlights the level of inaccuracy of musculoskeletal palpation skills and draws further attention to an area of much‐needed improvement in our musculoskeletal residency training programs. Ultrasound imaging is an effective noninvasive method for providing swift feedback to medical students and residents and thereby reduce the instances of inaccurate musculoskeletal palpation.